2019
DOI: 10.1093/gbe/evz172
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Extreme Environments in an Admixed Human Population from the Atacama Desert

Abstract: Inorganic arsenic (As) is a toxic xenobiotic and carcinogen associated with severe health conditions. The urban population from the Atacama Desert in northern Chile was exposed to extremely high As levels (up to 600 µg/l) in drinking water between 1958 and 1971, leading to increased incidence of urinary bladder cancer (BC), skin cancer, kidney cancer, and coronary thrombosis decades later. Besides, the Andean Native-American ancestors of the Atacama population were previously exposed for millennia to elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
(107 reference statements)
0
19
0
Order By: Relevance
“…(2010) . We used an SNP array data set from a previous study ( Vicuna et al. 2019 ) consisting of 185 admixed subjects (121 males and 64 females) with mostly European and Native American ancestry from the Atacama Region of Northern Chile.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2010) . We used an SNP array data set from a previous study ( Vicuna et al. 2019 ) consisting of 185 admixed subjects (121 males and 64 females) with mostly European and Native American ancestry from the Atacama Region of Northern Chile.…”
Section: Methodsmentioning
confidence: 99%
“…2019 ; Ko et al 2014 ). Further, a recent study found that PAS acting on Native American genetic variation may have aided a population with Native American and European ancestry from the Atacama Desert of Northern Chile to adapt to the pathophysiological effects of chronic exposure to high arsenic levels in water ( Vicuna et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAK16 encodes a ribosomal protein and plays an important role in ribosome biogenesis throughout the cell cycle [57]. In this study, it was found out that the mutations in MAK16 can induce the arrest of the cell cycle at G1 phase, during which the cell synthesizes mRNA and proteins as part of the preparation for cell division [58]. At present, there is still no role of MAK16 in the pathogenesis of tumors, which requires a further research to con rm.…”
Section: Discussionmentioning
confidence: 88%
“…MAK16 encodes a ribosomal protein and plays an important role in ribosome biogenesis throughout the cell cycle [ 76 ]. In this study, it was found that mutations in MAK16 can induce cell cycle arrest at G1 phase, during which the cell synthesizes mRNA and proteins in preparation for cell division [ 77 ]. At present, there is still no study of the role of MAK16 in the pathogenesis of tumours, which requires further research to confirm.…”
Section: Discussionmentioning
confidence: 99%